Genome sequencing of Bacillus thuringiensis isolate T414 toxic to pink bollworm (Pectinophora gossypiella Saunders) and its insecticidal genes. (September 2019) - Reyaz, A.L.; Balakrishnan, N.; Udayasuriyan, V.
Abstract: Bacillus thuringiensis is a spore-forming bacterium that is pathogenic towards a range of insect and nematode species and had been widely used as a biopesticide. In this study, we present the morphological, molecular and genetic characteristics of an indigenous Bt isolate T414 which displayed an effective toxicity against Pectinophora gossypiella . Scanning electron microscopy revealed the presence of bipyramidal, spherical and cubic shaped protein crystals in its spore-crystal suspension. SDS-PAGE analysis of its spore-crystal mixture showed the presence of two major protein bands viz. 130 and 65 kDa. Whole genome sequencing with MiSeq divulged that it contains a chromosome and many plasmids. The assembled genome finally contained 6493494bp. Automated annotation of this genome draft predicted 6877 coding sequences and 152 RNAs (rRNAs, tRNAs and ncRNAs). NCBI blast analysis showed that assembled genome was distributed in a chromosome and 15 different types of plasmids. Further analysis of draft sequence revealed it harbors parasporal crystal protein genes ( cry1Aa, cry1Ab, cry1Ac, cry1IAa, cry2Aa, cry2Ab and cyt1 ), vegetative insecticidal protein gene ( vip3Aa ), all plasmid borne and various additional virulence factors such as chitinases, proteases, bacteriocins and hemolysins. From the analysis it is evident that all the Cry, Cyt or Vip toxins are plasmid borne and are present on two types of plasmids named as p414A and p414E in the present study. A cry2A type gene was cloned and sequenced. It was named as cry2Aa21 by Bt nomenclature committee. Graphical abstract: Image 1 Highlights: Pink bollworm has developed resistance to Cry proteins in Bt cotton in India. An indigenous Bt isolate T414 has shown toxicity against pink bollworm using artificial diet bioassay. The whole genome sequence of the Bt isolate T414 revealed different kinds of insecticidal genes ( cry / vip ) .